1976
DOI: 10.1002/1097-0142(197608)38:2<994::aid-cncr2820380251>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Dental management of patients irradiated for oral cancer

Abstract: Management of patients irradiated for oral cancer should include consideration of their oral health prior to, and after, radiation therapy. Data from 130 patients, followed for a period of 1 to 10 years, are presented and evaluated. The philosophy of retention and maintenance of as many teeth as possible is supported by this data. Extraction of teeth with severe periodontal disease after irradiation also proves to be a relatively safe operation. Osteoradionecrosis tends to be limited in extent and is generally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
3

Year Published

1982
1982
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(32 citation statements)
references
References 10 publications
1
28
0
3
Order By: Relevance
“…Precautions to be followed in averting complications of radiotherapy at hospice of head & neck cancer patients [43,44]:…”
Section: Dental Caries and Periodontitissupporting
confidence: 78%
“…Precautions to be followed in averting complications of radiotherapy at hospice of head & neck cancer patients [43,44]:…”
Section: Dental Caries and Periodontitissupporting
confidence: 78%
“…Concerning local pathological conditions, marginal periodontitis (Niewald et al, 1996, Jereczek-Fossa and Orecchia, 2002, Katsura et al, 2008, Oh et al, 2009) and denture irritation (Thorn et al, 2000, Oh et al, 2009 have been implicated in the development of ORN. The reason is that an open wound is present in the oral cavity during and after RT in these cases (Regezi et al, 1976, Murray et al, 1980a, 1980c, Beumer et al, 1984, Kluth et al, 1988, Bachmann et al, 1996, Katsura et al, 2008.…”
Section: Other Factorsmentioning
confidence: 99%
“…Some studies have shown that the lack of pre-radiotherapy extractions presents a risk factor for ORN [28], while other studies have found that preradiotherapy extractions are not beneficial in reducing rates of ORN regardless of tooth condition [20] and may actually increase the overall risk of ORN [4,18,21,22]. 20 If extractions are performed, it is important to allow sufficient healing time prior to the commencement of radiotherapy but not to unduly delay it.…”
Section: Pre-radiotherapy Dental Management: Extractionsmentioning
confidence: 99%
“…We recommend that patients receive appropriate analgaesia for their pain, and are screened by a dietician to assess their oral intake. 21 …”
Section: Dental Management During Radiotherapy: Mucositismentioning
confidence: 99%
See 1 more Smart Citation